Evaluation of deoxypyridinoline levels in gingival crevicular fluid and serum as alveolar bone loss biomarker in patients with periodontitis - Suhail Syed; Vinathi Reddy Kankara; Krishnanjeya Reddy Pathakota; Preethi Krishnan; Ashank Mishra (Wolters Kluwer Medknow Publications, 2020)
Background: Several components of gingival crevicular fluid (GCF) reflect the course and predictability of periodontal disease and provide a pointer toward disease status. Potential biomarkers deoxypyridinoline (DPD), a metallophosphoesterase would correctly determine the presence of osteoclast-mediated bone turnover activity and seems to hold great promise as a predictive marker to determine bone destruction and active phases in the disease progression. Aim: The aim of the current study is proposed to investigate the biologic plausibility for the levels of DPD as biomarker in chronic periodontitis patients. Materials and Methods: The present cross-sectional study comprised 15 periodontally healthy and 15 chronic periodontitis patients who were age and genders matched, recruited from the outpatient department of Periodontics. GCF and blood samples for DPD estimation were collected from all the patients and analyzed using enzyme-linked immunosorbent assay kit. The clinical parameters such as clinical attachment loss (CAL), probing pocket depth (PPD), modified gingival index, bleeding index , and plaque index were recorded. Results: GCF DPD levels were significantly higher in chronic periodontitis patients when compared to periodontally healthy group. There were no significant correlations found among GCF and serum DPD levels with increasing age, gender, disease severity, and increase in PPD and CAL in both the groups. Conclusion: Within the limitations of this study, increased GCF DPD levels in chronic periodontitis can gauge ongoing periodontal destruction.